Comparative SARS-CoV-2 Omicron BA.5 variant and D614G-Wuhan strain infections in ferrets: insights into attenuation and disease progression during subclinical to mild COVID-19 - Barroso-Arévalo, Sandra; Sánchez-Morales, Lidia; Porras, Néstor; Díaz-Frutos, Marta; Barasona, Jose A.; Isla, Julio; López, Débora; Gortázar, Christian; Domínguez, Lucas; Sánchez-Vizcaíno, Jose M. (Frontiers in Veterinary Science, 2024)
Introduction As the SARS-CoV-2 virus continues to evolve and new variants emerge, it becomes crucial to understand the comparative pathological and immunological responses elicited by different strains. This study focuses on the original Wuhan strain and the Omicron variant, which have demonstrated significant differences in clinical outcomes and immune responses. Methods We employed ferrets as an experimental model to assess the D614G variant (a derivative of the Wuhan strain) and the Omicron BA.5 variant. Each variant was inoculated into separate groups of ferrets to compare disease severity, viral dissemination, and immune responses. Results The D614G variant induced more severe disease and greater viral spread than the Omicron variant. Notably, ferrets infected with the D614G variant exhibited a robust neutralizing antibody response, whereas those infected with the Omicron variant failed to produce a detectable neutralizing antibody response. Despite the clearance of the virus from nearly all tissues by 7 days post-infection, an increase in pathological lesions was observed from 14 to 21 days, particularly in those infected with the D614G variant, suggesting a sustained immune response even after viral clearance. Discussion These findings underscore the adaptability of SARS-CoV-2 and illuminate how susceptibility and clinical manifestations vary across different strains and species. The results emphasize the necessity of considering both the direct effects of viral infection and the indirect, often prolonged, impacts of the immune response in evaluating the outcomes of SARS-CoV-2 infections.